2B4 (CD244, SLAMF4) and CS1 (CD319, SLAMF7) in systemic lupus erythematosus and cancer - Malaer, Joseph D (Clinical immunology (Orlando, Fla.), 2019)
Copyright © 2018 Elsevier Inc. All rights reserved.